2017
DOI: 10.1515/gospo-2017-0043
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the possibility of mercury removal from hard coal with the use of air concentrating tables

Abstract: Mercury is characterized by highly toxic properties. The natural biogeochemical cycle of mercury occurs in the environment, which results in the fact that even a small amount of mercury emitted to the environment is a potential threat to human health. The process of coal combustion is one of the main sources of anthropogenic mercury emissions. For this reason, on 31 July 2017 the European Commission has adopted the mercury emission standards for large combustion plants. The issue of mercury emissions is partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…, it allows for the effective separation of pyrite grains from coal along with mercury occurring in them. The preliminary studies of the authors confirm the possibility of mercury removal from coal with the use of the FGX separator, with effectiveness up to 96% . However, it should be noted that for almost half of the analyzed coals, the effectiveness of mercury removal was much lower, i.e., even below 25%.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…, it allows for the effective separation of pyrite grains from coal along with mercury occurring in them. The preliminary studies of the authors confirm the possibility of mercury removal from coal with the use of the FGX separator, with effectiveness up to 96% . However, it should be noted that for almost half of the analyzed coals, the effectiveness of mercury removal was much lower, i.e., even below 25%.…”
Section: Introductionmentioning
confidence: 68%
“…The preliminary studies of the authors confirm the possibility of mercury removal from coal with the use of the FGX separator, with effectiveness up to 96%. 22 However, it should be noted that for almost half of the analyzed coals, the effectiveness of mercury removal was much lower, i.e., even below 25%. Such low effectiveness can be attributed to the occurrence of mercury in the overgrowth of pyrite on the organic matter of coal as well as in the organic matter itself.…”
Section: Introductionmentioning
confidence: 93%
“…We collected the existing Hg distribution in coal preparation plants from the literature, which is shown in Table . ,, The determination method of Hg distribution factors in thermal coal preparation is detailed in Supporting Information S1 . We found that these plants did not cover jig separation technology as well as small and medium coal preparation plants .…”
Section: Methodsmentioning
confidence: 99%
“…1. 14,21,22 The determination method of Hg distribution factors in thermal coal preparation is detailed in Supporting Information S1. 23 We found that these plants did not cover jig separation technology as well as small and medium coal preparation plants.…”
Section: Methodsmentioning
confidence: 99%
“…Particle size [ [250] , [251] , [252] , [253] ], feed rate [ 246 ], air flow rate [ 249 , 256 ], table transverse inclination [ 246 , 256 ], table longitudinal inclination [ 246 , 256 ], table vibration frequency [ 246 ], riffle height [ 246 ], and partition plate height [ 248 , [257] , [258] , [259] ] are the parameters that could affect the separation efficiency of both conventional air table and FGX separator (Table S4). FGX separator could also be applied to remove heavy metals like mercury from hard coal [ 254 ] and used for low-rank lignite beneficiation with the combination of subsequent infrared (IR) drying [ 250 ]. Regression model using response surface methodology (RSM) was applied for FGX separator to statistically optimize the separation [ 255 ].…”
Section: Dry-type Gravity Separation Technologiesmentioning
confidence: 99%